Leibniz’s Theory of the Origin of Numbers and the Mystery of the Trinity - Amunátegui, Godofredo Iommi (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Between the years 1678 and 1685 Leibniz composed two treatises entitled Circa Geometrica Generalia (C.G.G.) and Notationes Generales (N.G.) where he presented a cryptic theory of the origin of positive integers closely related to the Mystery of the Trinity.This work aims at giving an interpretation of Leibniz’s mathematical ideas in terms of the concept of determinatio. Use is made of such an hypothesis in order to clarify the theological import of Leibniz’s conception.